Measuring unbearable psychache in suicide risk: psychometric evidence for the Italian UP3 and comparison with the psychache scales - Bungaro, Nicole; Dattilo, Laura; Innamorati, Marco; Balsamo, Michela; Blandizzi, Cecilia; Alessio, Chiara; De Vincenzo, Francesco; Quinto, Rossella Mattea; Genova, Federica; Contardi, Anna; Carlucci, Leonardo (Frontiers in Psychology, 2025)
IntroductionPsychache, or mental pain, is considered an independent predictor of suicide risk. Recent perspectives highlight the unbearable aspect of psychache as an imminent trigger for suicidal crisis. To assess this specific dimension, the Unbearable Psychache Scale (UP3) was developed from the original Psychache Scale (PAS). Although preliminary studies investigated UP3’s psychometric properties, its discriminant validity in assessing suicide risk remains unclear.MethodsThus, two cross-sectional studies were conducted on Italian community samples to examine the factorial structure, internal consistency, and scalability of the Italian UP3, and to compare its incremental and discriminant validity with PAS13/PAS10 in identifying individuals at risk for suicide.ResultsStudy #1 (N = 707) confirmed the UP3’s unidimensional structure, with good model fit, internal consistency, and scalability. In Study #2 (N = 257), the UP3 correlated moderately to strongly with PASs, depression, and suicide risk. ROC analyses indicated that UP3 achieved comparable accuracy to PAS13 and PAS10 for recent suicide risk (AUCs 0.75–0.83), but lower accuracy for lifetime suicidal ideation (AUC = 0.681) and behaviors (AUC = 0.777). Sensitivity analyses revealed that UP3 prioritized sensitivity over specificity, with low Positive Predictive Values across outcomes: PPV was 0.42 for recent suicidal ideation, and 0.21 for recent suicidal behaviors, compared with slightly higher but still limited values for PAS scales. Hierarchical models showed that UP3 did not demonstrate incremental validity over PAS13 in predicting either recent or lifetime suicide risk.DiscussionThe UP3 appears particularly sensitive to acute unbearable psychache, performing better in detecting recent than lifetime suicide risk. Although it does not outperform PAS scales, the UP3’s brevity and focus on the intolerable component of psychache make it suitable for use alongside other measures as part of a comprehensive suicide risk evaluation in clinical or large-scale contexts.